Pengaruh Pendekatan Pembelajaran Realistic Mathematics Education Terhadap Pemahaman Konsep Matematika Siswa Kelas VII Di SMP Negeri 3 Tondano - Wulandari Laurensia Mujono; Victor R. Sulangi; Patricia V. J. Runtu (Departement of Mathematics Education, 2023)
This research aims to improve students' understanding of mathematical concepts in Comparative material by using the Realistic Mathematics Education approach, in this case there is an increase in learning outcomes before being given treatment and after being given Realistic Mathematics Education treatment on the average value. The type of research used is experimental research, and the research design used is The One Shot Case Study Design. This research was carried out at SMP Negeri 3 Tondano. The research subjects were 30 students of class VII B as an experimental class who were treated with a Realistic Mathematics Education approach. The average posttest result for the experimental class was 84.13. The results of hypothesis testing using the t-test concluded that the average learning outcomes of students who were taught using the Realistic Mathematics Education approach were higher than the average learning outcomes of students who were not taught using the Realistic Mathematics Education approach.